Theocracy - Connolly, Sean J. (Systems of government, 2017)
"Describes what the theocratic system of government is, how religions play a role in the laws and morals of the citizens. The history of how theocracies have evolved, the rise and fall of religions, and the future of theocratic governments are examined." -- Provided by publisher